Unraveling Firms: Demand, Productivity and Markups Heterogeneity - Emanuele Forlani; Ralf Martin; Giordano Mion; Mirabelle Muls (Center for Economic Studies and ifo Institute (CESifo), 2016)
We develop a new econometric framework that simultaneously allows recovering heterogeneity in demand, TFP and markups across firms while leaving the correlation among the three unrestricted. We do this by systematically exploiting assumptions that are implicit in previous firm-level productivity estimation approaches. We use Belgian firms production data to quantify TFP, demand and markups and show how they are correlated among them, across time and with measures obtained from other approaches. We also show to what extent our three dimensions of heterogeneity allow us to gain deeper and sharper insights on two key firm-level outcomes: export status and size.
Keywords: D24; L11; L25; F14; 330; demand; productivity; markups; production function estimation; export status; firm size